Nursing management of rebound hyperglycemia after pulmonary surgery: A case report of patient with coronary heart disease and type 2 diabetes mellitus (1例冠心病和合并2型糖尿病患者肺部手术后反跳性高血糖的护理与思考) - LI Pengping (李鹏萍) (Journal of International Translational Medicine Limited, 2021)
This paper reviewed the nursing measures of rebound hyperglycemia after pulmonary surgery in a patient with coronary heart disease and type 2 diabetes mellitus. Key issues of nursing included blood glucose management, continuous renal replacement treatment and nursing, enteral nutrition care, skin care and airway management。 (本文回顾1例冠心病和合并2型糖尿病患者肺部手术后反跳性高血糖的护理措施, 包括血糖管理、连续性肾脏替代治疗(CRRT)护理、肠内营养护理、皮肤护理和气道管理。)